A comparative analysis of stress, anxiety, and social well-being of working mothers and stay-at-home mothers during the covid pandemic - Zahra Nadri; Fatemeh Torabi; Masoume Pirhadi (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: The role of mental health is crucial in maintaining the dynamism and productivity of any given society. In contemporary times, a significant proportion of the workforce is comprised of women and mothers. Working in healthcare facilities, where exposure to pathogenic agents is an everyday nuisance, can have detrimental effects on mothers' stress and anxiety levels. Furthermore, such exposure can also endanger the health of both the family and society. Conversely, the employment of mothers could positively impact their social well-being. The primary objective of this study is to assess and compare the stress, anxiety, and social well-being scores of mothers employed in healthcare facilities and stay-at-home mothers during the COVID pandemic. MATERIALS AND METHODS: This study is a cross-sectional analysis of 246 mothers, equally divided into two groups: Mothers who work in health centers and stay-at-home mothers (123 individuals in each group). The study was conducted from 2021 to 2022, a multistage sampling method was utilized and two questionnaires were administered: The DASS 21 (21 questions) and the social well-being questionnaire (48 questions). The data were analyzed using SPSS 18, and descriptive and analytical tests (Independent Samples T-Test, Mann-Whitney) were employed. RESULTS: The mean age was 35.7 ± 7.1 for working mothers and 34.3 ± 6.3 for stay-at-home mothers. The average stress score for employed mothers was 5.72 ± 4.7, and for stay-at-home mothers, it was 7.16 ± 4.3, which indicates a statistically significant difference in stress levels between the two groups (P = 0.04). However, the two groups had no significant difference in the mean anxiety score (P = 0.08). The mean score for social well-being was 165.5 ± 18.4 for working mothers and 162.17 ± 21.2 for stay-at-home mothers. This difference was not statistically significant (P = 0.18). Except for the social acceptance dimension (P = 0.003), no statistically significant differences were observed in the social well-being dimension between the two groups. CONCLUSION: The social acceptance of working mothers appears to be greater than that of stay-at-home mothers. Higher social acceptance suggests that they hold a more positive outlook on people and are at ease in social situations, which may have helped to alleviate their stress and anxiety.